2014
DOI: 10.5152/tpa.2014.1815
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of some physical hazards which may affect health in primary schools

Abstract: Aim: This study was performed with the objective to determine the levels of some physical hazards in primary schools. Material and Methods:This study is a cross-sectional field survey. In this study which was conducted in 31 primary schools selected by appropriate sampling from the district of Keçiören of the province of Ankara, measurements related with temperature, light, electromagnetic field (EMF) and noise levels were done at hundreds of points. Approval was obtained from Gülhane Military Medical Faculty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The total number of classrooms in schools is 624, and in our study, measurements were made in 203 (32.5%) classrooms. The classroom selection criteria in schools has been made by investigating two classrooms from the right and left sides of each hall from each floor, starting from the top floor, for schools that have a single building; and for schools that have two separate buildings, by investigating one classroom that is closest to the end of the staircases from each hall in each floor, starting from the top floor, separately from each building (13). The study was obtained from the Kocaeli University Clinical Research Ethics Committee with the decision number 4/18, dated 27.11.2015.…”
Section: Materials and Methods Population And Samplementioning
confidence: 99%
See 1 more Smart Citation
“…The total number of classrooms in schools is 624, and in our study, measurements were made in 203 (32.5%) classrooms. The classroom selection criteria in schools has been made by investigating two classrooms from the right and left sides of each hall from each floor, starting from the top floor, for schools that have a single building; and for schools that have two separate buildings, by investigating one classroom that is closest to the end of the staircases from each hall in each floor, starting from the top floor, separately from each building (13). The study was obtained from the Kocaeli University Clinical Research Ethics Committee with the decision number 4/18, dated 27.11.2015.…”
Section: Materials and Methods Population And Samplementioning
confidence: 99%
“…Studies conducted in Turkey have shown that schools have significant deficiencies in compliance with environmental health standards (13)(14)(15)(16). In this study, it was aimed to evaluate the effects of physical environment characteristics of schools on students' success and absenteeism.…”
mentioning
confidence: 99%
“…Interestingly, it plays an important role in preventive and curative management [1], The main component of the School Health programme is health service which has been continuing as an integral part of it [9]. Which term refers to services for students and staff of the school to the promotion of health and development, prevention, early detection of, and intervention for physical, psychological, and social factors affecting young children and all workers in school [10], that will reflect positively on academic performance [11]. It has been involved in a wide range of activities to prevent and control infectious diseases that affect young children, and also contributed to activities related to mental health, supervision of health, and record keeping [12].…”
Section: Introductionmentioning
confidence: 99%